If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -5 + 2i)(x + 5 + 2i) = 0 Reorder the terms: (-5 + 2i + x)(x + 5 + 2i) = 0 Reorder the terms: (-5 + 2i + x)(5 + 2i + x) = 0 Multiply (-5 + 2i + x) * (5 + 2i + x) (-5(5 + 2i + x) + 2i * (5 + 2i + x) + x(5 + 2i + x)) = 0 ((5 * -5 + 2i * -5 + x * -5) + 2i * (5 + 2i + x) + x(5 + 2i + x)) = 0 ((-25 + -10i + -5x) + 2i * (5 + 2i + x) + x(5 + 2i + x)) = 0 (-25 + -10i + -5x + (5 * 2i + 2i * 2i + x * 2i) + x(5 + 2i + x)) = 0 Reorder the terms: (-25 + -10i + -5x + (10i + 2ix + 4i2) + x(5 + 2i + x)) = 0 (-25 + -10i + -5x + (10i + 2ix + 4i2) + x(5 + 2i + x)) = 0 (-25 + -10i + -5x + 10i + 2ix + 4i2 + (5 * x + 2i * x + x * x)) = 0 Reorder the terms: (-25 + -10i + -5x + 10i + 2ix + 4i2 + (2ix + 5x + x2)) = 0 (-25 + -10i + -5x + 10i + 2ix + 4i2 + (2ix + 5x + x2)) = 0 Reorder the terms: (-25 + -10i + 10i + 2ix + 2ix + 4i2 + -5x + 5x + x2) = 0 Combine like terms: -10i + 10i = 0 (-25 + 0 + 2ix + 2ix + 4i2 + -5x + 5x + x2) = 0 (-25 + 2ix + 2ix + 4i2 + -5x + 5x + x2) = 0 Combine like terms: 2ix + 2ix = 4ix (-25 + 4ix + 4i2 + -5x + 5x + x2) = 0 Combine like terms: -5x + 5x = 0 (-25 + 4ix + 4i2 + 0 + x2) = 0 (-25 + 4ix + 4i2 + x2) = 0 Solving -25 + 4ix + 4i2 + x2 = 0 Solving for variable 'i'. The solution to this equation could not be determined.
| 16+(y+9)= | | 3+x=5+2x | | 8+11=-7-19 | | y=-4(1)-2 | | 8-5d=-37 | | 3x+1=7(x+2) | | -4(-1)+2y=-2 | | (5p^3-3)+(2p^2-3p^3)= | | (17+33)+x= | | y=-4(-1)-2 | | 3x+1=1(x+6) | | 3x+1=3(x+3) | | x^2+2=11 | | 11+28+19= | | 2y-4=4y+5-2y | | x^2+22x+20=0 | | 327*6*0= | | 2y-4=4y+5-2x | | x^7+8x^4+16x=0 | | 5x-7y=-64 | | 4(x-7)=3x+5 | | 2y-4=3x(2-x)-2 | | (6a)10= | | 10y+0=6y+10 | | 2y-4=5(x-3)-2x | | .375x+4=1.5x | | 15(x-2)=15x-23+9 | | 4+9+7/2-(5+8)= | | .375x+4=1.5 | | 5x-10=3x+30 | | 0=4x^2+x-1 | | 10sin^2(x)=3 |